Mental Disorders in Danish Hospital Registers: A Review of Content and Possibilities for Epidemiological Research - Plana-Ripoll O; Liu X; Köhler-Forsberg O; Sørensen HT; Momen NC (Clinical Epidemiology)
Oleguer Plana-Ripoll,1,2 Xiaoqin Liu,2 Ole Köhler-Forsberg,3,4 Henrik Toft Sørensen,1 Natalie C Momen5 1Department of Clinical Epidemiology, Center for Population Medicine, Aarhus University and Aarhus University Hospital, Aarhus, Denmark; 2National Centre for Register-based Research, Department of Public Health, Aarhus University, Aarhus, Denmark; 3Department of Clinical Medicine, Aarhus University, Aarhus, Denmark; 4Psychosis Research Unit, Aarhus University Hospital Psychiatry, Aarhus, Denmark; 5Department of Clinical Epidemiology, Aarhus University and Aarhus University Hospital, Aarhus, DenmarkCorrespondence: Natalie C Momen, Email ncm@clin.au.dkBackground: The Danish national hospital registers are a rich source of data for psychiatric epidemiology. The potential to identify diagnosed mental disorders in the Danish population has resulted in a plethora of important research studies. However, no recent review of these research sources exists.Objective: To review the content, data quality and epidemiological considerations regarding mental disorders in the Danish hospital registers.Methods: We provide information on the setting, history, and data access regarding mental disorders in the Danish hospital registers (defined according to the International Classification of Diseases, Tenth Revision, F group Mental and behavioural disorder codes). We describe the registration of mental disorders over time in the Danish hospital registers, by providing counts of individuals diagnosed with mental disorders each year, by types of mental disorders, diagnosis, hospital contact, and contact unit. We also provide information on considerations when using these data sources, including data quality. For this, we searched PubMed to identify validation studies of coding of mental disorder diagnoses.Results: Between 1969 and 2022, 1,136,280 individuals (10.7% of all individuals who resided in Denmark in this period) have been registered as having a mental disorder as a primary or secondary diagnosis in a psychiatric unit in Denmark at least once. The type of contact and unit diagnoses were made in varied by mental disorder type. The literature indicates that a large proportion of coded diagnoses in the Danish hospital registers of mental disorders were considered valid.Conclusion: We provide an overview of the available data for investigating mental disorders in the Danish hospital registers. We raise awareness of the limitations researchers should be aware of when using this data and discuss their implications. Careful consideration should be given to these during study design and when reporting findings from register-based studies on diagnosed mental disorders.Keywords: epidemiological methods, mental disorders registries, research design, validation studies